FISHERY AND BIOLOGY OF POMADASYS HASTA (BLOCK) - Deshmukh, V M (Indian Journal of Fisheries, 2011)
The Biology and Fishery of Pomadasys hasta (Bloch) has been described. Thespecies exhibited single restricted spawning period during October to December. Theminimumsizeof maturity was found to be 41.0 cm. The fish had shown intermittantfeeding habit, feeding mainly on Crustacea like Squilla, crab and prawns and also Teleosteanfish. Length-frequency and otolith data had been used to trace the growth andassess the age of the flsh. The growth rate was found to be 22.0 cm, in the first year^12.0 cm, each in the second and third years; 6.0 cm, and 4.0 cm in the fourth and fifthyears respectively. The fishery for the species extended from September to June witha peak season in November to February. The Kutch and Dwarka regions were richfishing grounds for the species.